Fine particulate matter PM2.5 generated by building demolition increases the malignancy of breast cancer MDA-MB-231 cells. (February 2021) - Cheng, Chun-Wen; Sheu, Gwo-Tarng; Chou, Jing-Shiuan; Wang, Pei-Han; Cheng, Yu-Chun; Lai, Chane-Yu
Abstract: Objectives: This study investigates the effects of water-extracted PM2.5 on a triple-negative breast cancer (TNBC) cell line, MDA-MB-231, by sampling suspended particulates around a building demolition site. Methods: PM2.5 particles were obtained using a high-flow TISCH sampler. Water-soluble PM2.5 were extracted by an ultrasonic oscillator and then freeze-dried. The heavy metal components of soluble PM2.5 was analyzed by ICP-MS. Cell viability was evaluated by MTT assay for cells that were exposed to PM2.5 (200, 400 and 600 μg/mL). Wound healing and transwell cell migration and invasion assays were used to measure cell motility and the invasiveness of cancer cells that had been exposed to PM2.5 into a chemo-attractant substance. Interrelated mechanisms of cancer malignancy were analyzed by Western blot analysis. Results: Nearby PM2.5 concentrations increased significantly during the deconstruction of buildings, and the Cd, Cu, Pb, Zn and Cr contents of soluble PM2.5 also significantly increased. Following exposure to PM2.5, the survival rate of breast cancer cells was significantly higher than that of the control group. Soluble PM2.5 -treated cells had a higher migration capacity. The signaling pathway of FAK/PI3K/AKT proteins was more activated in PM2.5 -treated cells than the control group. Increased levels of Aurora B and Bcl-2 were associated with cell proliferation. Elevated levels of cathepsins D, β-catenin, N-cadherin, vimentin and MMP-9 were associated with breast cancer cell metastasis. Conclusion: Soluble PM2.5 from building demolition may promote/progress in surviving TNBC cells, increasing the malignancy of breast cancer. This study offered evidence of a link between demolition PM2.5 and cancer progression. Graphical abstract: Image 1 Highlights: Building demolition generates large amount of PM2.5 containing elevated concentrations of heavy metals. Water-extracted PM2.5 promotes triple negative breast cancer cell proliferation and migration. Water-extracted PM2.5 enhances the PI3K/Akt signal transduction pathway in MDA-MB-231 cells.